Atmospheric input of inorganic nitrogen and phosphorus to the Ligurian Sea: Data from the Cap Ferrat coastal time-series station. (December 2015) - de Fommervault, Orens Pasqueron; Migon, Christophe; Dufour, Aurélie; D'Ortenzio, Fabrizio; Kessouri, Fayçal; Raimbault, Patrick; Garcia, Nicole; Lagadec, Véronique
Abstract: Atmospheric fluxes of bio-available inorganic nitrogen (DIN, i.e . nitrate+ammonium) and phosphorus (DIP, i.e . phosphate) were measured in 2010, 2011 and 2013 at the sampling station of Cap Ferrat (Ligurian Sea). Wet and dry fluxes of DIN, averaged over three years, were 35 and 19 mmol m −2  yr −1, respectively. Most of the nitrate was deposited under dry form, whilst ammonia was twice more found in wet deposition. Wet and dry fluxes of DIP, averaged over three years, were 0.11 and 0.64 mmol m −2  yr −1, respectively. Atmospheric fluxes of DIN and DIP were compared with other photic zone nutrient input sources, physical and biological, i.e . winter convection, N2 fixation, and upward diffusion. Even if convection is by far the most important nutrient input for surface waters, atmospheric sources may be the second one, supplying more nutrients than diazotrophy and diffusion, particularly in conditions of water column stratification. Highlights: Nitrogen atmospheric fluxes are more controlled by the wet mode. Nitrate is more deposited under dry form, ammonia under wet form. Phosphorus atmospheric fluxes are more controlled by the dry mode. Atmospheric deposition strongly impacts Mediterranean molar ratios N/P. Atmosphere supplies more nutrients to surface waters than diazotrophy or diffusion.